The Da Vinci Code
Harvard professor Robert Langdon receives an urgent late-night phone call while on business in Paris: the elderly curator of the Louvre has been brutally murdered inside the museum.Alongside the body, police have found a series of baffling codes.As Langdon and a gifted Frenchcryptologist, Sophie Neveu, begin to sort through the bizarre riddles, they are stunned to find a trail that leads to the works of Leonardo Da Vinci - and suggests the answer to a mystery that stretches deep into the vault of history.Unless Langdon and Neveu can decipher the labyrinthine code and quickly assemble the pieces of the puzzle, a stunning historical truth will be lost forever.